Knowledge of Chlamydia Trachomatis Assessed in a Puerto Rican Medical Student Population - Lopez-Cepero, Ronald; Flores, Juan A.; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2011)
Objective: The knowledge of medical students in Puerto Rico with regard to the Chlamydia trachomatis infection has not been formally assessed. The purpose of this study was to make such an assessment as it is the members of this group who will eventually educate and inform patients about this and other health-care issues. Methods: The sample was drawn from a population of students enrolled in a four-year medical school program in Puerto Rico. Data were collected via a selfadministered one-page questionnaire and took approximately 5 minutes to complete. The questionnaire was a 9-item inventory composed mostly of knowledge items. A frequency count for each item was calculated. The SPSS program was used for the statistical analysis. Results: A final response rate of 76% (338/455) was obtained for the analysis. The sources of chlamydial information were college (73.4%), high school (59.8%), friends (28.1%), press media (21.6%), and family members (15.4%). Asked to identify the etiology of the infection, participants responded that it was bacterial (78.1%), viral (16.9%), parasitic (3.8%), or fungal (1.2%). Knowledge about the existence of a cure for the infection resulted in 85.5% of the respondents answering in the affirmative, that a cure exists; the rest either did not know or were uncertain about the existence of a cure for Chlamydia. Knowledge regarding the mode of transmission resulted in 98.2% stating that it is transmitted sexually, while public bathrooms as a source of infection accounted for 2.4%; kissing (1.5%) was also identified as a method of transmission. Statistics for the symptoms and the consequences of chlamydia resulted in pelvic inflammatory disease (PID) (81.1%), infertility (75.1%), abnormal vaginal secretions (79.6%), burning sensation upon urination (49.6%), ectopic pregnancies (44.9%), abnormal vaginal bleeding (13.9%), and cervical cancer (8.9%). Conclusion: Our data suggest that members of this population understand this infection only partially and that there is indeed a lack of knowledge regarding infection of sexually transmitted Chlamydia trachomatis. Without accurate knowledge of chlamydial infection, medical students and physicians are unable to identify its presence and, subsequently, educate their patients regarding both the management and the serious complications of this infection. There are serious implications for women’s health, and thus knowledge is important to reduce the burden of chlamydial infection.